The Effect of Agitation Techniques with Increasing Natrium Hypochlorite Temperature on Bovine Pulp Tissue Dissolution - Michell Wijaya Koesuma; Bernard Ongki Iskandar (Faculty of Dentistry, Universitas Trisakti, 2025)
Background: Root canal irrigation is one of the most determining factors that affect the success of a root canal treatment. Natrium hypochlorite (NaOCl) is the most commonly used root canal irrigants, which, in high concentrations, increases the risk of irritation to the periradicular tissues and oral mucosa if extrusion occurs. Low concentration NaOCl with increased temperature and agitation techniques could reduce the risk of irritation. Objective: To evaluate the effect of agitation techniques with the increased temperature of natrium hypochlorite on bovine pulp tissue dissolution capacity. Method: Twenty-five pulp tissues of bovine mandibular incisors (n = 5 per group) were weighed and then placed individually in Eppendorf test tubes containing the following irrigants: NaCl 0.9%; NaOCl 5% at 25°C; NaOCl 5% at 60°C. Group 1 NaCl 0.9% received no further treatment. Group 2 NaOCl 5% at 25°C agitated with sonic. Group 3 NaOCl 5% at 60°C agitated with sonic. Group 4 NaOCl 5% at 25°C agitated with ultrasonic. Lastly, Group 5 NaOCl 5% at 60°C agitated with ultrasonic. Dissolution speed was calculated by dividing the difference between initial pulp weight and after-treatment pulp weight (mg) by the period of time (sec). Result: NaOCl 5% at 60°C agitated with the ultrasonic group and showed the best result at dissolving pulp tissue. Conclusion: Increased temperature of natrium hypochlorite showed no significant difference toward bovine pulp tissue dissolution, while sonic and ultrasonic agitation techniques showed a significant difference toward bovine pulp tissue dissolution.